2006
DOI: 10.1007/s11250-006-4266-y
|View full text |Cite
|
Sign up to set email alerts
|

The small East African shorthorn zebu cows in Kenya. I: Linear body measurements

Abstract: Assessment of genetic diversity is a prerequisite for the management and conservation of animal genetic resources. Appropriate design of breeding programmes is therefore impossible for breeds that have not been adequately characterized either phenotypically and/or genetically. Phenotypic characteristics are important in breed identification and classification in ways that farming communities can relate with. This study phenotypically characterized two breeds of zebu cattle in Kenya. A total of 12 measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 14 publications
(22 reference statements)
5
51
0
2
Order By: Relevance
“…Among the linear type traits, the highest correlation was observed between WH and RH (r =0.98) while the lowest estimate (r =0.51) was recorded for RH and SW. Similar findings have been reported [10,12,24]. The strong relationship existing between BW and body measurements suggests that either or combination of these morphological traits could be used to estimate live weight in cattle fairly well in the situation where weighbridges or scales are not available.…”
Section: Pairwise Correlationssupporting
confidence: 86%
“…Among the linear type traits, the highest correlation was observed between WH and RH (r =0.98) while the lowest estimate (r =0.51) was recorded for RH and SW. Similar findings have been reported [10,12,24]. The strong relationship existing between BW and body measurements suggests that either or combination of these morphological traits could be used to estimate live weight in cattle fairly well in the situation where weighbridges or scales are not available.…”
Section: Pairwise Correlationssupporting
confidence: 86%
“…The calculation of the correlation coefficients showed that live weight was highly correlated with HG compared to other measurements, which clearly indicated that HG is the most reliable measurement for prediction of live weight of Brahman crossbred cattle. This is in agreement with the findings of other studies which reported high correlation coefficient between live weight and heart girth measurement (Msangi et al, 1999;Malau-Aduli et al, 2004;Nwacharo et al, 2006;Abdelhadi and Babiker, 2009;Yakubu, 2010). The strong relationship found between BW and body measurements in this study suggests that either or combination of these morphological traits could be used to estimate live weight in cattle fairly well in the situation where weighbridges or scales are not available.…”
Section: Discussionsupporting
confidence: 93%
“…Appropriate design of breeding programmes is impossible for breeds that have not been adequately characterized either phenotypically and/or genetically (Mwacharo et al, 2006). Phenotypic characteristics are important in breed identification and classification.…”
Section: Introductionmentioning
confidence: 99%